Neuropsychiatric Outcomes in UK Military Veterans With Mild Traumatic Brain Injury and Vestibular Dysfunction. Issue 1 (January 2020) - Denby, Emma; Murphy, Dominic; Busuttil, Walter; Sakel, Mohamed; Wilkinson, David
Abstract : Objective: To estimate the frequency of vestibular dysfunction following blunt, blast, and combined blunt and blast mild traumatic brain injury (mTBI) and thereon assess the long-term impact of vestibular dysfunction on neurobehavioral function and disability independently of comorbid psychiatric symptoms. Setting: Combat Stress residential and Veterans' Outreach drop-in centers for psychological support. Participants: One hundred sixty-two help-seeking UK military veterans. Main Measures: Self-reported frequency and severity of mTBI (using the Ohio State TBI Identification Method), Vertigo Symptom Scale, PTSD Checklist for DSM-5, Kessler Psychological Distress Scale (K10), Neurobehavioral Symptom Inventory, Headache Impact Test (HIT6), Memory Complaints Inventory, World Health Organization Disability Assessment Schedule II short version (WHODAS 2.0). Results: Seventy-two percent of the sample reported 1 or more mTBIs over their lifetime. Chi-square analyses indicated that vestibular disturbance, which affected 69% of participants, was equally prevalent following blunt (59%) or blast (47%) injury and most prevalent following blunt and blast combined (83%). Mediation analysis indicated that when posttraumatic stress disorder, depression, and anxiety were taken into account, vestibular dysfunction in participants with mTBI was directly and independently associated with increased postconcussive symptoms and functional disability. Conclusion: Vestibular dysfunction is common after combined blunt and blast mTBI and singularly predictive of poor long-term mental health. From a treatment perspective, vestibular rehabilitation may provide relief from postconcussive symptoms other than dizziness and imbalance. Abstract : Supplemental Digital Content is Available in the Text.